Rainfall erosivity factors, runoff, soil losses under Cerrado conditions - Dedecek, Renato Antonio (Pesquisa Agropecuaria Brasileira, 2014)
To establish the best rainfall erosivity factor related to runoff and soil losses, data from 116 rainstorms obtained from runoff plots in fallow condition on a Dark-Red Latosol (Haplustox) clay textured and with 5.5% slope were used. Seventeen erosivity indexes combining rainfall characteristics: amount, intensity and energy, and four factors estimating soil moisture were tested. There was an increase on the correlation coefficients of all erosivity indexes, when rainstorm data were classified into convective and frontal. Results indicate that a soil loss of 1 t/ha and 1 mm of runoff required 79 mm and 74 mm of rainfall, respectively, considering convective rains. In case of frontal rains, 49 mm and 41 mm of rainfall were needed to cause the same losses. The IEK (intensivity-energy) erositivity index was best correlated (r2 = 0.90) to runoff at both rain types. EK (energy) was best estimator (r2 = 0.78) of soil losses when rain was convective, while R10 (intensity-amount) showed best correlation (r2 = 0.59) to soil losses at frontal rain types. Considering those situations in general, EI30 was the best erosivity index.